2016
DOI: 10.1002/ldr.2659
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of a Protected Area on Hedgerow Conservation: The Case of a Spanish Cultural Landscape

Abstract: Hedgerows are key features in agricultural landscapes performing diverse functions that are both economically and ecologically significant. Here, we quantify how the characteristics of a relict hedgerow network of a Spanish cultural landscape (Guadarrama mountains in the north of Madrid region) have changed over a single decade both inside and outside the boundaries of a Protected Area, the aim of which is to conserve cultural uses and biodiversity. A gradient of abandonment of pasture systems was detected, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
1
24
0
2
Order By: Relevance
“…However, until recently, cultural landscapes have been forgotten or misinterpreted in PAs [13,35] and in practice, the management of some PAs related to cultural landscapes does not seem to be effective with respect to this conservation objective [62]. This study reveals inconsistencies in the regulations that hinder the achievement of conservation objectives linked to the protection of cultural landscapes [25,48,63]. Several studies in the Mediterranean region highlight that PAs' policies restrict rural activities, such as traditional grazing, resulting in the decrease and loss of natural and biocultural diversity [64,65] and the promotion of rural abandonment [44].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, until recently, cultural landscapes have been forgotten or misinterpreted in PAs [13,35] and in practice, the management of some PAs related to cultural landscapes does not seem to be effective with respect to this conservation objective [62]. This study reveals inconsistencies in the regulations that hinder the achievement of conservation objectives linked to the protection of cultural landscapes [25,48,63]. Several studies in the Mediterranean region highlight that PAs' policies restrict rural activities, such as traditional grazing, resulting in the decrease and loss of natural and biocultural diversity [64,65] and the promotion of rural abandonment [44].…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the overlapped area is regulated by both the management categories of national and regional parks, which differ in their protection status and the administration in charge, as well as in the elapsed time since their declaration and establishment. The conservation objectives of both PAs intend to protect the biodiversity and ecological processes that are maintained by a highly threatened, traditional, silvicultural landscape, although, according to previous studies, these goals are not being fully achieved [44,45,48,49].…”
Section: Study Areamentioning
confidence: 99%
“…In fact, although around 40% of empirical studies reported both biophysical and sociological variables, only the half tried to develop tools to integrate both sets of variables. These efforts were mainly accomplished using geographic information systems, multivariate analysis, and mathematical models, such as multiple regression analysis [6,[40][41][42] or Bayesian networks [43][44][45]. Thus, there is room for developing SES studies by using analyses that combine both sets of variables at different spatial and temporal scales.…”
Section: The Matter Of Socio-ecological Systems: What Who How and mentioning
confidence: 99%
“…The landscape structure of the area has been the result of ancient land use systems and rural activities that for centuries have been performed in the region contributing to their great socio-ecological value [20], which have made them worthy of different categories of protection. Thus, the Lozoya valley is within the boundaries of the Sierra …”
Section: Study Areamentioning
confidence: 99%
“…They are people of mature age without special incentives to visit the area, although have a certain preference for activities related to nature, such as watching birds, other animals, vegetation, nature photography, ...; ii) Ruralnaturalist visitors (25%), show preference for natural and rural-cultural landscapes. They are young people (16)(17)(18)(19)(20)(21)(22)(23)(24) who visit these places for their rural landscape, for sport or simply enjoy nature or have a picnic; iii) Family tourism visitors (21%), attracted by both natural as cultural values, especially water landscapes; and iv) Indifferent visitors (28%), with little motivation to visit the valley -a sociologically heterogeneous group, without concrete preferences for any landscape type or landscape component. Table 1(a) shows the two first discriminant functions indicating the degree of preference, indifference or rejection of a set of variables that represent characteristics of the landscape in 2007.…”
Section: Typology Of Visitors In 2007mentioning
confidence: 99%